Factors of sustainable intensification in agriculture of Ukraine: evidence from the enterprises of the Kharkivska oblast - Strapchuk, Svitlana І.; Mykolenko, Olena P.; Страпчук, Світлана Іванівна; Миколенко, Олена Петрівна (Мукачево: Вид-во МДУ, 2021)
Reducing the negative impact of agricultural enterprises' activities on the environment with an increase in food demand can be achieved by implementing sustainable intensification measures, where the key measure is an increase in crop yields while reducing the use of resources. The purpose of this study is to identify the factors of sustainable intensification of agricultural enterprises in Ukraine by building a model of the interdependence of yield on the level of diversity of agricultural crops, application of organic fertilisers, availability of animal husbandry on the farm, labour costs, mineral fertilisers and depreciation, the use of fuel materials per 1 ha and the level of payback of costs. During the scientific study, a sample of 516 enterprises of the Kharkivska Oblast that grow agricultural products was processed; some of them are engaged in animal husbandry. Using the correlation and regression analysis method, data was analysed and processed using specialised Microsoft Excel and SPSS 21 software. The paper presents a model of the dependence of the yield of agricultural enterprises of the Kharkivska Oblast on numerous factors that were selected based on the theoretical provisions of the sustainable intensification of agriculture. It was found out that the diversity of agricultural crops, the application of organic fertilisers, the availability of animal husbandry on the farm, and labour costs are considerable factors and have both a positive and negative impact on yield. The model applied the effect of interaction between two factors, which showed the greatest impact on the dependent variable. The study provides reasoning for the availability of the highest yield among enterprises that additionally engage in economic activities for raising animals, as well as specialise in the production of various crops. The practical significance of the results obtained lies in the provision of proposals on the areas of sustainable intensification of agricultural enterprises in Ukraine. Зниження негативного впливу діяльності підприємств сільського господарства на навколишнє середовище за умови зростання потреби в продовольстві може бути забезпечене шляхом впровадження заходів сталої інтенсифікації, де ключовим вимірником є збільшення урожайності культур за умови зменшення використання ресурсів. Метою дослідження є виявлення чинників сталої інтенсифікації сільськогосподарських підприємств України шляхом побудови моделі взаємозалежності урожайності від рівня різноманіття сільськогосподарських культур, внесення органічних добрив, наявності тваринництва у господарстві, витрат на оплату праці, мінеральні добрива та амортизацію, використання паливних матеріалів на 1 га та рівня окупності витрат. Під час проведення наукового дослідження опрацьовано вибірку з 516 підприємств Харківської області, що вирощують сільськогосподарську продукцію; деякі з них займаються тваринництвом. За допомогою методу кореляційно-регресійного аналізу здійснено аналіз та обробку даних з використанням спеціалізованих програм Microsoft Excel та SPSS 21. У роботі представлено модель залежності урожайності сільськогосподарських підприємств Харківської області від низки чинників, які були обрані, спираючись на теоретичні положення сталої інтенсифікації сільського господарства. З’ясовано, що різноманіття сільськогосподарських культур, внесення органічних добрив, наявність тваринництва в господарстві, витрати на оплату праці є значущими чинниками та здійснюють як позитивний, так і негативний вплив на урожайність. У моделі було застосовано ефект взаємодії двох чинників, який продемонстрував найбільший вплив на залежну змінну. Обґрунтовано наявність найвищої урожайності у підприємств, що додатково здійснюють господарську діяльність з вирощування тварин, а також спеціалізуються на виробництві різноманітних культур. Практична значущість отриманих результатів полягає в наданні пропозицій щодо напрямів сталої інтенсифікації сільськогосподарських підприємств України.
Чинники сталої інтенсифікації у сільському господарстві України на прикладі підприємств Харківської області
Svitlana І. Strapchuk - corresponding author
Keywords: Research Subject Categories::FORESTRY, AGRICULTURAL SCIENCES and LANDSCAPE PLANNING; Research Subject Categories::SOCIAL SCIENCES; sustainable development; circular economy; agricultural enterprises; correlation-regression model; сталий розвиток; циркулярна економіка; аграрні підприємства; кореляційно-регресійна модель